عقيدة القضاء والقدر ودورها في بناء شخصية المسلم - كرمادي, إحسان; محده, سكينة; بوخزنة, مروة; قسوم, مريم (جامعة الوادي university of eloued, 2018)
عقيدة القضاء والقدر أحد أصول الإيمان الستة ,وواجب الإيمان بها ,كما لا يتم الإيمان إلا بالإيمان بمتضمناتها وىي بما تسمى بمراتبو الأ برع, ودليل ىذا مذكور في كتاب الله عز وجل وسنة نبيو محمد صلى الله عليه وسلم. والإيمان بهذا الركن ليس مفتاحا لأن نخوض فيو ونحتج بو على ذنوبنا ,فهذا لا يجوز. لكن المؤمن بهذه العقيدة إيمانا صحيحاتنعكس عليو بنتائج سارة وثمرات طيبة عقديا وأخلاقيا ونفسيا . The doctrine of the judiciary is one of the tenets of faith and the duty of faith in it, as faith is only done by believing in its contents. It is in the so-called four orders. The evidence of this is mentioned in the Book of Allaah and the Sunnah of His Prophet Muhammad (peace and blessings of Allaah be upon him) It is not permissible for him to do so. But the believer in this faith is a healthy belief, and it is reflected in good results and good results, .both morally and morally
عقيدة